Comparative Causal Analysis of the Effects of Long-Acting Muscarinic Antagonist Versus No Long-Acting Bronchodilator Use on Readmission or Mortality After Hospitalization for Chronic Obstructive Pulmonary Disease - Melissa H. Roberts; Douglas W. Mapel; Hans Petersen (Adis, Springer Healthcare, 2019)
Abstract Background Retrospective observational studies may provide real-world evidence about long-acting muscarinic receptor antagonist (LAMA) effectiveness in reducing mortality or COPD-related readmission risk after a COPD hospitalization. Causal inference and competing risk statistical procedures aid in managing confounding and competing outcome events that complicate retrospective analyses. Objective To compare COPD-related readmission and mortality risk among patients receiving a LAMA versus patients receiving no long-acting bronchodilator ("no LABD") within 30 days post-discharge. Methods This retrospective observational analysis of patients (aged ≥ 40 years) hospitalized for COPD used claims data (years 2004-2012). Events occurring during the period from 31 days through 12 months post-discharge were compared. The hazard ratio (HR) for the combined outcome of COPD-related readmission or mortality was estimated using Cox regression. Confounding was addressed using inverse probability of treatment weighting (IPTW). The competing risk of non-COPD-related readmission was considered. Results 10,405 COPD patients were included (LAMA = 751, no LABD = 9654). IPTW achieved a balanced sample (10,518 LAMA, 10,405 no LABD). Unweighted HR (LAMA vs no LABD) for COPD-related readmission or death, adjusted for age, sex, comorbidities, and baseline utilization, was 1.00 [95% confidence interval (CI) 0.84, 1.20]. Weighted (IPTW) adjusted HR was 0.94 (95% CI 0.88, 1.00). Unweighted and weighted HRs further adjusted for competing risk were 0.97 (95% CI 0.82, 1.16) and 0.91 (0.86, 0.98), respectively. Conclusions Bias by indication and comorbidities make the measurement of retrospective COPD treatment effectiveness difficult. Using IPTW and additionally considering the competing event risk, LAMA use was associated with a small reduction in risk for COPD-related readmission or death over the period from 31 days to 12 months post-discharge.